Solar light conversion silicon-containing backboard material and preparation method thereof
By using modified PVDF and high heat dissipation AlN in the photovoltaic backplane outer layer material, the shortcomings of traditional photovoltaic backplane materials in terms of weather resistance, adhesion and cost are solved, and higher weather resistance, mechanical strength and crack resistance are achieved, and the service life of photovoltaic modules is extended.
Patent Information
- Application Number
- CN202510390175.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional photovoltaic backplane outer materials have shortcomings in terms of weather resistance, adhesion and cost, resulting in limited service life and overall performance of photovoltaic modules.
Polyvinylidene fluoride (PVDF) is used as the matrix material, and the modification is made by adding fluorosilicone resin, and AlN with high heat dissipation ability is added as filler to form a PVDF/siloxane copolymer, and its compatibility and dispersion with the organic matrix are improved by the preparation method of modified AlN.
The weather resistance, mechanical strength and crack resistance of the photovoltaic backplane are improved, their adaptability under different climatic conditions is enhanced, and the service life of photovoltaic modules is extended by improving thermal conductivity and light scattering capabilities.
Smart Images

Figure CN119899477A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photovoltaic back panels, and specifically refers to a solar light conversion silicon-containing back panel material and a preparation method thereof. Background Art
[0002] Photovoltaic backsheet is an important component of photovoltaic modules. Its main function is to protect solar cell modules from environmental factors (such as moisture, ultraviolet rays, oxygen, mechanical stress, etc.), while providing electrical insulation and mechanical support to ensure the long-term stable operation of photovoltaic modules. Photovoltaic backsheets are usually composed of a three-layer structure, including an inner layer (adhesive layer), a middle layer (base layer), and an outer layer (weather-resistant layer). Among them, the outer layer plays a vital role in the overall performance of the photovoltaic backsheet and determines the durability and environmental adaptability of the backsheet. Inner layer (adhesive layer): The main function is to provide adhesive properties so that the backsheet can be firmly attached to the packaging material of the module (such as EVA or POE) to prevent delamination and peeling. Common materials include modified PET (polyethylene terephthalate), PVDF (polyvinylidene fluoride) or special adhesives. Middle layer (base layer): Mainly provides mechanical support and electrical insulation properties, usually made of PET film or other high molecular polymer materials. PET has good insulation, mechanical strength and heat resistance, so it is widely used. The outer layer is the most critical part of the photovoltaic backsheet, which is mainly responsible for providing weather resistance, UV resistance, moisture and heat resistance, and mechanical protection. It is directly exposed to the external environment and needs to have strong anti-aging properties to ensure that the photovoltaic modules can operate for a long time without being damaged by the external environment.
[0003] The following materials are commonly used for the outer layer of traditional photovoltaic backplanes: PVDF (polyvinylidene fluoride): It has excellent weather resistance, UV resistance and chemical stability, but its bonding performance with the PET layer is poor and it is prone to delamination problems. In addition, the price of PVDF materials is relatively high, which increases the manufacturing cost of photovoltaic modules. FEVE (fluoroethylene-vinyl ether copolymer): It has the weather resistance and good bonding performance of PVDF, but it may still degrade after long-term exposure to strong ultraviolet rays. PET (polyethylene terephthalate): Although traditional PET materials have high mechanical strength, they have poor weather resistance and are prone to aging, yellowing and cracking after long-term exposure to ultraviolet rays.
[0004] The outer layer of the photovoltaic backsheet is crucial to the weather resistance, service life and overall performance of the photovoltaic module. Although traditional PVDF and PET materials can provide protection to a certain extent, they still have problems such as poor adhesion, yellowing, and easy aging. Summary of the invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a solar energy conversion silicon-containing backplane material and a preparation method thereof. The backplane material provided by the present invention uses polyvinylidene fluoride as a base material, and the polyvinylidene fluoride base material is modified by adding fluorosilicone resin. At the same time, AlN with high heat dissipation capacity is used as a filler. The high thermal conductivity of AlN reduces the temperature rise of the photovoltaic module, thereby reducing the decrease in photoelectric conversion efficiency caused by excessively high temperature.
[0006] In order to achieve the above-mentioned object, the technical scheme adopted by the present invention is as follows: the present invention proposes a solar light conversion silicon-containing backboard material, and the raw materials for preparing the silicon-containing backboard material include the following components in parts by weight: 50-70 parts of VDF, 4-6 parts of perfluorooctyltrimethoxysilane, 2-8 parts of tetraethyl orthosilicate, 4-6 parts of KH570, 1-2 parts of modified AlN, 3-5 parts of emulsifier, 5-10 parts of perfluorohexyl iodide, 1-2 parts of buffer, 1-3 parts of initiator, and 0.5-1.5 parts of auxiliary agent;
[0007] Preferably, the emulsifier includes at least one of sodium lauryl sulfate, sodium laureth sulfate, Tego Wet 265, and BYK-348;
[0008] Preferably, the buffer comprises at least one of NaHCO3 and NH4HCO3;
[0009] Preferably, the initiator comprises at least one of ammonium persulfate, sodium persulfate, and potassium persulfate;
[0010] Preferably, the auxiliary agent includes at least one of sodium bisulfite and ferrous sulfate;
[0011] Preferably, the preparation method of the modified AlN specifically comprises the following steps:
[0012] A1. Dissolve 3-glycidyloxypropyltriethoxysilane in DMSO, stir the mixture at 200-300 rpm under nitrogen atmosphere, slowly drop 4-aminoimidazole, mix well, add TEA to adjust the pH to 8-9, raise the reaction temperature to 40-50°C, stir the mixture for 4-8h, remove the reaction solvent by distillation under reduced pressure, add ethyl acetate for washing, and purify to obtain grafted triethoxysilane;
[0013] Preferably, in step A1, the added mass of the 4-aminoimidazole is 28%-43% of the mass of 3-glycidyloxypropyltriethoxysilane;
[0014] Preferably, in step A1, the mass concentration of 3-glycidyloxypropyltriethoxysilane in DMSO is 20-28 mg / mL;
[0015] Preferably, in step A1, the mass concentration of 4-aminoimidazole in DMSO is 40-60 mg / mL;
[0016] A2, adding AlN to a planetary ball mill, adding ethanol solution, and ball milling at a speed of 600-800 rpm. After 1-2 hours, adding the grafted triethoxysilane prepared in step S1, and continuing the ball milling. After 3-5 hours, after the ball milling is cooled, placing it at 120-150° C. for vacuum drying. After drying for 10-12 hours, modified AlN is obtained;
[0017] Preferably, in step A2, the ethanol solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 10-20:1;
[0018] Preferably, in step A2, the mass volume ratio between the AlN and the ethanol solution is 1.1-1.8 g / mL;
[0019] Preferably, in step A2, the mass volume ratio between the AlN and the grafted triethoxysilane is 6-10 g / mL;
[0020] The present invention also provides a method for preparing a solar light-converting silicon-containing backplane material, which specifically comprises the following steps:
[0021] S1. Dissolve perfluorooctyltrimethoxysilane, ethyl orthosilicate and KH570 in anhydrous ethanol, mix well, raise the reaction temperature to 70-80°C, adjust the pH of the reaction system to 4-5 with HCl, stir the reaction at 150-180 rpm, add 50-70 mL of deionized water dropwise, continue the reaction for 5-7 hours, and remove the reaction solvent by rotary evaporation to obtain a siloxane reaction solution;
[0022] S2, add deionized water, emulsifier and buffer to the reactor, introduce nitrogen, add the siloxane reaction solution prepared in step S1, stir the siloxane reaction solution at 400-500 rpm to disperse it evenly, add perfluorohexyl iodide at room temperature, increase the temperature to 70-90°C, add VDF, maintain the reaction temperature, add initiator and auxiliary agent, react for 6-8h, cool to room temperature, remove unreacted substances, add ethanol / NaCl aqueous solution for washing, adjust the pH to 3-4, place at room temperature for static sedimentation treatment, vacuum filter, wash with anhydrous ethanol and deionized water in turn, and vacuum dry to obtain PVDF / siloxane copolymer;
[0023] S3, adding the modified AlN into DMF, adding K2CO3, and fully dispersing the modified AlN at a speed of 300-400 rpm to obtain an activated modified AlN solution;
[0024] Preferably, in step S3, the mass concentration of AlN in DMF is 10-20 mg / mL;
[0025] Preferably, in step S3, the mass ratio between K2CO3 and modified AlN is 0.3-0.5:1;
[0026] S4, dissolving the PVDF / siloxane copolymer prepared in step S2 in DMF, raising the temperature to 80-100°C, fully dissolving the PVDF / siloxane copolymer at a speed of 200-300rpm, adding dropwise the activated modified AlN solution prepared in step S3, raising the reaction temperature to 100-120°C, stirring the reaction at a speed of 400-600rpm for 12-24h, cooling to room temperature, adding deionized water for washing, filtering, washing with anhydrous ethanol and ethyl acetate in sequence, and vacuum drying to obtain a photovoltaic backplane material.
[0027] The beneficial effects achieved by the present invention are as follows:
[0028] The present invention provides a solar light-converting silicon-containing backplane material and a preparation method thereof. The backplane material provided by the present invention uses polyvinylidene fluoride as a base material, modifies the polyvinylidene fluoride base material by adding fluorosilicone resin, and uses AlN with high heat dissipation capacity as a filler. The high thermal conductivity of AlN reduces the temperature rise of photovoltaic modules, thereby reducing the decrease in photoelectric conversion efficiency caused by excessive temperature. In the present invention, active functional groups are introduced by reacting 3-glycidyloxypropyltriethoxysilane with 4-aminoimidazole, and imidazole groups are introduced into siloxane. A planetary ball mill is used to combine the AlN surface with the siloxane through a Si-O-Al bond, introduce imidazole active groups into the AlN surface, enhance its compatibility with the organic matrix, enhance the dispersibility of AlN particles, improve its uniform distribution in the photovoltaic backplane, and reduce particle agglomeration, thereby improving the thermal conductivity of the backplane material. In the present invention, a siloxane reaction solution is formed by a hydrolysis-polycondensation reaction of perfluorooctyltrimethoxysilane, ethyl orthosilicate and KH570, the double bond groups on KH570 are retained, the pH is controlled between 4 and 5 to ensure the stability of the siloxane structure, VDF monomer is added to the reaction system under nitrogen protection, and polymerization is initiated under temperature control conditions to form a copolymer structure of PVDF and siloxane, and the PVDF / siloxane copolymer is stirred and reacted with an activated modified AlN solution at a high temperature, and the final material is obtained after washing and drying. The introduction of perfluorosilane enhances the hydrophobicity of the backplane, improves its antifouling and weather resistance, and the siloxane skeleton improves the backplane material The heat resistance is improved and the high-temperature aging problem is reduced. The PVDF matrix ensures good mechanical strength and weather resistance and provides the basic support for the backplane. The introduction of the siloxane phase improves the flexibility of PVDF and improves its resistance to UV aging and moisture and heat. The addition of perfluorohexyl iodoethane enables the PVDF / siloxane copolymer to form an iodine-terminated structure. The interaction between I and the imidazole group further enhances the hydrophobicity of PVDF and ensures the uniformity of AlN in the final composite material to avoid local over-concentration or agglomeration. At the same time, the overall thermal conductivity is improved. The uniform distribution of AlN improves the thermal conductivity of the backplane, allowing the components to dissipate heat faster and reduce power attenuation. The presence of the siloxane phase improves the light scattering ability, allowing more solar energy to be effectively absorbed by photovoltaic cells. The high thermal conductivity of AlN reduces the temperature rise of photovoltaic modules, thereby reducing the decrease in photoelectric conversion efficiency caused by excessive temperature. The high thermal conductivity of AlN enables the photovoltaic backplane to have faster heat diffusion ability, reduce efficiency attenuation caused by high temperature, and increase the life of photovoltaic modules. Through the coupling effect of KH570, PVDF and siloxane are tightly combined, which improves the mechanical strength and crack resistance of the material and is suitable for applications under different climatic conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the modified AlN prepared in Example 1 of the present invention;
[0030] Figure 2 FTIR image of the product prepared in steps S1 and S2 of Example 1 of the present invention;
[0031] Figure 3 The mechanical properties of the backplane materials prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in the figure;
[0032] Figure 4 This is a graph showing the heat dissipation performance results of the backplane materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-3.
[0033] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0036] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.
[0037] Example 1
[0038] The present embodiment provides a solar light conversion silicon-containing backplane material, wherein the raw materials for preparing the silicon-containing backplane material include the following components in parts by weight: 50 parts of VDF, 4 parts of perfluorooctyltrimethoxysilane, 2 parts of ethyl orthosilicate, 4 parts of KH570, 1 part of modified AlN, 3 parts of sodium dodecyl sulfate, 5 parts of perfluorohexyl iodide, 1 part of NaHCO3, 1 part of ammonium persulfate, and 0.5 parts of sodium bisulfite;
[0039] The preparation method of modified AlN specifically comprises the following steps:
[0040] A1. Accurately weigh 1.4 g of 3-glycidyloxypropyltriethoxysilane and place it in a flask, add 50 mL of DMSO, and after the 3-glycidyloxypropyltriethoxysilane is completely dissolved, nitrogen is introduced for 30 min, and the reaction is stirred at 300 rpm. Accurately weigh 0.4 g of 4-aminoimidazole is dissolved in 10 mL of DMSO, and added dropwise to the reaction system at 1 mL / min. After sufficient mixing, TEA is added to adjust the pH of the reaction system to 9.0, and the reaction temperature is increased to 50° C. After reacting for 4 hours, the reaction solvent is removed by distillation under reduced pressure, and the mixture is repeatedly washed with ethyl acetate three times, and activated by column chromatography to obtain grafted triethoxysilane;
[0041] A2. Accurately weigh 20 g of AlN and place it in a planetary ball mill. Mix 10 mL of anhydrous ethanol and 1 mL of deionized water evenly, add the mixture into the ball milling jar of the planetary ball mill, and perform ball milling at a speed of 600 rpm. After 1 hour, add 2 mL of the grafted triethoxysilane prepared in step S1, and continue to perform ball milling at a speed of 600 rpm. After 4 hours, after the ball milling reaction system is cooled, place it at 150° C. for vacuum drying. After 12 hours, modified AlN is obtained.
[0042] The modified AlN prepared in this example was observed using a JSM-6380LV scanning electron microscope. Figure 1 This is a SEM image of the modified AlN prepared in Example 1 of the present invention. As shown in the figure, due to ball milling and silane modification, the degree of agglomeration between AlN particles is reduced, showing a more uniform distribution state. After grafting triethoxysilane, a non-uniform silicon oxide film may be attached to the surface of the AlN particles, making the surface structure rougher.
[0043] The present invention also provides a method for preparing a solar light-converting silicon-containing backplane material, which specifically comprises the following steps:
[0044] S1. Accurately weigh 4 g of perfluorooctyltrimethoxysilane, 2 g of ethyl orthosilicate and 4 g of KH570 into a three-necked flask, add 20 mL of anhydrous ethanol as a solvent, and after the reactants are completely dissolved, use 1 M HCl aqueous solution to adjust the pH of the reaction system to 4.5, add an oil bath to the reaction system to a temperature of 70° C., stir the reaction at a speed of 180 rpm, and add 60 mL of deionized water to the reaction system at a speed of 1 mL / min. After the addition of deionized water is completed, continue the reaction for 6 h. After the reaction is completed, wait for the reaction system to cool to room temperature, and then remove the excess reaction solvent by rotary evaporation to obtain a silicon-oxygen reaction solution;
[0045] S2, add 2L of deionized water to the reactor, add 3g of sodium dodecyl sulfate and 1g of NaHCO3, mix until the emulsifier and buffer are completely dissolved, pass flowing nitrogen for 30min to remove oxygen in the reactor, add the siloxane reaction solution prepared in step S1, stir at 400rpm until the reaction system is uniform, add 5g of perfluorohexyl iodide at room temperature, mix evenly, increase the temperature to 80°C, maintain the pressure in the reactor at 3.5MPa, pass VDF at 10g / min, maintain the reaction temperature at 80°C, add 1g of ammonium persulfate and 0.5g of sodium bisulfite, stir thoroughly at 400rpm, react until the pressure in the reactor drops to 0.1MPa, add VD F until the pressure in the kettle is 3.5MPa, repeat the operation until the weight of VDF is reached, after reacting for 6h, when the cumulative pressure drop reaches 0.5MPa, stop heating, remove the VDF that reacts externally, collect the reaction product, prepare ethanol / NaCl aqueous solution (ethanol: 10vol%, NaCl: 2.5wt%) for washing, adjust the pH of the reactant system to 4.0, place it at room temperature for static sedimentation treatment, when no precipitation is generated, use vacuum filtration to collect the solid, wash it repeatedly with anhydrous ethanol and deionized water three times in sequence, and place it at 40°C for vacuum drying for 24h to obtain PVDF / siloxane copolymer;
[0046] Nicolet Fourier transform infrared spectrometer was used to analyze the polymer molecular structure of the siloxane reaction solution and PVDF / siloxane copolymer prepared in steps S1 and S2. The sample was flattened by KBr. Figure 2 FTIR images of the products prepared in steps S1 and S2 of Example 1 of the present invention, A is the siloxane reaction solution prepared in step S1, and B is the PVDF / siloxane copolymer prepared in step S2. As shown in the figure, at 1100-1090cm -1 The Si-O-Si stretching vibration absorption peak appears at 1270-1250cm -1 The infrared characteristic absorption peak of CF appears at 1650-1610cm -1 The infrared special absorption peak of C=C appears at , while in image B, this peak is not obvious or does not exist, indicating that the double bond structure in the siloxane reaction solution has polymerized with VDF;
[0047] S3, accurately weigh 1 g of modified AlN and place it in a beaker, add 10 mL of DMF to evenly disperse the AlN, add 0.3 g of K2CO3, and fully disperse the modified AlN at a speed of 400 rpm to obtain an activated modified AlN solution;
[0048] S4, dissolving the PVDF / siloxane copolymer prepared in step S2 in 100 mL of DMF, raising the temperature to 100° C., fully dissolving the PVDF / siloxane copolymer at a speed of 200 rpm, adding dropwise the activated modified AlN solution prepared in step S3, raising the reaction temperature to 100° C., stirring at a speed of 400 rpm for 24 hours, cooling to room temperature, adding deionized water for washing, filtering, washing with anhydrous ethanol and ethyl acetate in sequence, and vacuum drying to obtain a photovoltaic backplane material.
[0049] Example 2
[0050] The present embodiment provides a solar light conversion silicon-containing backplane material, wherein the raw materials for preparing the silicon-containing backplane material include the following components in parts by weight: 60 parts of VDF, 5 parts of perfluorooctyltrimethoxysilane, 5 parts of ethyl orthosilicate, 2 parts of KH570, 1.5 parts of modified AlN, 4 parts of sodium lauryl polyether sulfate, 7 parts of perfluorohexyl iodide, 1.5 parts of NaHCO3, 2 parts of sodium persulfate, and 1 part of sodium bisulfite;
[0051] The preparation method of modified AlN specifically comprises the following steps:
[0052] A1. Accurately weigh 1.4 g of 3-glycidyloxypropyltriethoxysilane and place it in a flask, add 60 mL of DMSO, and after the 3-glycidyloxypropyltriethoxysilane is completely dissolved, nitrogen is introduced for 30 minutes, and the reaction is stirred at a speed of 200 rpm. Accurately weigh 0.5 g of 4-aminoimidazole and dissolve it in 10 mL of DMSO, and add it dropwise to the reaction system at 1 mL / min. After sufficient mixing, TEA is added to adjust the pH of the reaction system to 8.0, and the reaction temperature is increased to 45° C. After reacting for 8 hours, the reaction solvent is removed by reduced pressure distillation, and the mixture is repeatedly washed with ethyl acetate three times, and activated by column chromatography to obtain grafted triethoxysilane;
[0053] A2. Accurately weigh 16 g of AlN and place it in a planetary ball mill. Mix 10 mL of anhydrous ethanol and 0.5 mL of deionized water evenly, add the mixture into the ball milling jar of the planetary ball mill, and perform ball milling at 800 rpm. After 2 h, add 2 mL of the grafted triethoxysilane prepared in step S1, and continue to perform ball milling at 800 rpm. After 3 h, after the ball milling reaction system is cooled, place it at 150 ° C for vacuum drying. After 12 h, modified AlN is obtained.
[0054] The present invention also provides a method for preparing a solar light-converting silicon-containing backplane material, which specifically comprises the following steps:
[0055] S1. Accurately weigh 5 g of perfluorooctyltrimethoxysilane, 5 g of ethyl orthosilicate and 2 g of KH570 into a three-necked flask, add 25 mL of anhydrous ethanol as a solvent, and after the reactants are completely dissolved, use 1 M HCl aqueous solution to adjust the pH of the reaction system to 4, add an oil bath to the reaction system to a temperature of 75°C, and stir the reaction at a speed of 150 rpm. Add 50 mL of deionized water to the reaction system at a speed of 1 mL / min. After the addition of deionized water is completed, continue the reaction for 7 h. After the reaction is completed, wait for the reaction system to cool to room temperature, and then remove the excess reaction solvent by rotary evaporation to obtain a silicon-oxygen reaction solution;
[0056] S2, add 2L of deionized water to the reactor, add 4g of sodium laureth sulfate and 1.5g of NaHCO3, mix until the emulsifier and buffer are completely dissolved, pass flowing nitrogen for 30min to remove oxygen in the reactor, add the siloxane reaction solution prepared in step S1, stir at 500rpm until the reaction system is uniform, add 7g of perfluorohexyl iodide at room temperature, mix evenly, increase the temperature to 70°C, maintain the pressure in the reactor at 3.5MPa, pass VDF at 10g / min, maintain the reaction temperature at 70°C, add 2g of sodium persulfate and 1g of sodium bisulfite, stir thoroughly at 500rpm, react until the pressure in the reactor drops to 0.1MPa, add VD F until the pressure in the kettle is 3.5MPa, repeat the operation until the weight of VDF is reached, after reacting for 7h, when the cumulative pressure drop reaches 0.5MPa, stop heating, remove the VDF that reacts externally, collect the reaction product, prepare ethanol / NaCl aqueous solution (ethanol: 10vol%, NaCl: 2.5wt%) for washing, adjust the pH of the reactant system to 3.0, place it at room temperature for static sedimentation treatment, when no more precipitation is generated, use vacuum filtration to collect the solid, wash it repeatedly with anhydrous ethanol and deionized water three times in sequence, and place it at 40°C for vacuum drying for 24h to obtain PVDF / siloxane copolymer;
[0057] S3, accurately weigh 1.5 g of modified AlN and place it in a beaker, add 10 mL of DMF to evenly disperse the AlN, add 0.4 g of K2CO3, and fully disperse the modified AlN at a speed of 400 rpm to obtain an activated modified AlN solution;
[0058] S4. Dissolve the PVDF / siloxane copolymer prepared in step S2 in 100 mL of DMF, raise the temperature to 100° C., fully dissolve the PVDF / siloxane copolymer at a speed of 300 rpm, add dropwise the activated modified AlN solution prepared in step S3, raise the reaction temperature to 120° C., stir the reaction at a speed of 600 rpm for 12 hours, cool to room temperature, add deionized water for washing, filter, wash with anhydrous ethanol and ethyl acetate in sequence, and obtain a photovoltaic backplane material after vacuum drying.
[0059] Example 3
[0060] The present embodiment provides a solar energy conversion silicon-containing backplane material, wherein the silicon-containing backplane material comprises the following components in parts by weight: 70 parts of VDF, 6 parts of perfluorooctyltrimethoxysilane, 8 parts of ethyl orthosilicate, 6 parts of KH570, 2 parts of modified AlN, 5 parts of BYK-348, 10 parts of perfluorohexyl iodide, 3 parts of NH4HCO, 3 parts of potassium persulfate, and 1.5 parts of sodium bisulfite;
[0061] The preparation method of modified AlN specifically comprises the following steps:
[0062] A1. Accurately weigh 1.4 g of 3-glycidyloxypropyltriethoxysilane and place it in a flask, add 70 mL of DMSO, and after the 3-glycidyloxypropyltriethoxysilane is completely dissolved, nitrogen is introduced for 30 minutes, and the reaction is stirred at a speed of 250 rpm. Accurately weigh 0.6 g of 4-aminoimidazole and dissolve it in 10 mL of DMSO, and add it dropwise to the reaction system at 1 mL / min. After sufficient mixing, TEA is added to adjust the pH of the reaction system to 8.5, and the reaction temperature is increased to 40° C. After reacting for 6 hours, the reaction solvent is removed by reduced pressure distillation, and the mixture is repeatedly washed with ethyl acetate three times, and activated by column chromatography to obtain grafted triethoxysilane;
[0063] A2. Accurately weigh 12 g of AlN and place it in a planetary ball mill. Mix 10 mL of anhydrous ethanol and 0.8 mL of deionized water evenly, add the mixture into the ball milling jar of the planetary ball mill, and perform ball milling at 700 rpm. After 1.5 h, add 2 mL of the grafted triethoxysilane prepared in step S1, and continue to perform ball milling at 700 rpm. After 5 h, after the ball milling reaction system is cooled, place it at 150 ° C for vacuum drying. After 12 h, modified AlN is obtained.
[0064] The present invention also provides a method for preparing a solar light-converting silicon-containing backplane material, which specifically comprises the following steps:
[0065] S1. Accurately weigh 6 g of perfluorooctyltrimethoxysilane, 8 g of ethyl orthosilicate and 6 g of KH570 into a three-necked flask, add 30 mL of anhydrous ethanol as a solvent, and after the reactants are completely dissolved, use 1 M HCl aqueous solution to adjust the pH of the reaction system to 5, add an oil bath to the reaction system temperature to 80° C., stir the reaction at a speed of 180 rpm, and add 70 mL of deionized water to the reaction system at a speed of 1 mL / min. After the addition of deionized water is completed, continue the reaction for 5 h. After the reaction is completed, wait for the reaction system to cool to room temperature, and then remove the excess reaction solvent by rotary evaporation to obtain a siloxane reaction solution;
[0066] S2, add 2L of deionized water to the reactor, add 3g of sodium dodecyl sulfate and 1g of NaHCO3, mix until the emulsifier and buffer are completely dissolved, pass flowing nitrogen for 30min to remove oxygen in the reactor, add the siloxane reaction solution prepared in step S1, stir at 450rpm until the reaction system is uniform, add 5g of perfluorohexyl iodide at room temperature, mix evenly, increase the temperature to 90°C, maintain the pressure in the reactor at 3.5MPa, pass VDF at 10g / min, maintain the reaction temperature at 90°C, add 1g of ammonium persulfate and 0.5g of sodium bisulfite, stir thoroughly at 450rpm, react until the pressure in the reactor drops to 0.1MPa, add VD F until the pressure in the kettle is 3.5MPa, repeat the operation until the weight of VDF is reached, after reacting for 8h, when the cumulative pressure drop reaches 0.5MPa, stop heating, remove the VDF that reacts externally, collect the reaction product, prepare ethanol / NaCl aqueous solution (ethanol: 10vol%, NaCl: 2.5wt%) for washing, adjust the pH of the reactant system to 3.5, place it at room temperature for static sedimentation treatment, when no more precipitation is produced, use vacuum filtration to collect the solid, wash it repeatedly with anhydrous ethanol and deionized water three times in sequence, and place it at 40°C for vacuum drying for 24h to obtain PVDF / siloxane copolymer;
[0067] S3, accurately weigh 2 g of modified AlN and place it in a beaker, add 10 mL of DMF to evenly disperse the AlN, add 0.5 g of K2CO3, and fully disperse the modified AlN at a speed of 400 rpm to obtain an activated modified AlN solution;
[0068] S4. Dissolve the PVDF / siloxane copolymer prepared in step S2 in 100 mL of DMF, raise the temperature to 100° C., fully dissolve the PVDF / siloxane copolymer at a speed of 250 rpm, add dropwise the activated modified AlN solution prepared in step S3, raise the reaction temperature to 110° C., stir the reaction at a speed of 500 rpm for 18 h, cool to room temperature, add deionized water for washing, filter, wash with anhydrous ethanol and ethyl acetate in sequence, and obtain a photovoltaic backplane material after vacuum drying.
[0069] Comparative Example 1
[0070] This comparative example provides a photovoltaic backplane material and a preparation method thereof, which differs from Example 1 only in that the backplane material comprises the following components in parts by weight: 50 parts of PVDF, 4 parts of perfluorooctyltrimethoxysilane, 6 parts of ethyl orthosilicate, 1 part of modified AlN, 3 parts of sodium dodecyl sulfate, and 1 part of NaHCO3; step S2 of the preparation method of the backplane material is modified to "fully mix the PVDF and the siloxane reaction solution prepared in step S1 in DMF to obtain a PVDF / siloxane blend"; step S4 of the preparation method of the backplane material is modified to "dissolve the PVDF / siloxane blend prepared in step S2 in 100 mL of In DMF, the temperature was raised to 100°C, the PVDF / siloxane copolymer was fully dissolved at a speed of 250 rpm, the activated modified AlN solution prepared in step S3 was added dropwise, the reaction temperature was raised to 110°C, the reaction was stirred at a speed of 500 rpm for 18 hours, the reaction was cooled to room temperature, deionized water was added for washing, and after filtering, anhydrous ethanol and ethyl acetate were used for washing in sequence, and after vacuum drying, a photovoltaic backplane material was obtained. The remaining components and component contents were the same as those in Example 1.
[0071] Comparative Example 2
[0072] This comparative example provides a photovoltaic backplane material and a preparation method thereof, which differs from Example 1 only in that the modified AlN is replaced by the same weight of AlN in the backplane material, the preparation method is the same as that in Example 1, and the remaining components and component contents are the same as those in Example 1.
[0073] Comparative Example 3
[0074] This comparative example provides a photovoltaic backplane material and a preparation method thereof, which differs from Example 1 only in that, in step A1 of the preparation method of the modified AlN, 3-glycidyloxypropyltriethoxysilane is replaced with the same mass of tetraethyl orthosilicate, and at the same time, step A1 does not contain 4-aminoimidazole. The preparation method thereof is the same as that of Example 1, and the remaining components, component contents, and preparation method are the same as those of Example 1.
[0075] Experimental Example 1
[0076] In this experimental example, the mechanical properties of Examples 1-3 and Comparative Examples 1-3 were measured. The photovoltaic backplane materials prepared in Examples 1-3 and Comparative Examples 1-3 were melt-extruded by a twin-screw extruder, cooled and granulated, and cast into films to prepare finished film samples with a thickness of 20 μm. The samples were tested for tensile strength and elongation at break using a universal mechanical testing machine according to the method in GB / T 1040.3-2006 with a tensile rate of 100 mm / min. The backplane materials in Examples 1-3 and Comparative Examples 1-3 were irradiated in a UV aging box for 300 kWh / m 3 After aging, the tensile strength and elongation at break were tested;
[0077] Figure 3 The mechanical properties result diagram of the backplane materials prepared by Examples 1-3 of the present invention and Comparative Examples 1-3 is shown in the figure. As shown in the figure, the mechanical properties of the backplane materials described in Examples 1-3 are significantly higher than those of Comparative Examples 1-3. Compared with the Comparative Examples, in the backplane materials prepared by Examples 1-3 of the present invention, the fluorosilicone resin containing double bonds is copolymerized with VDF to form an iodine-terminated copolymer, and the AlN modified by the imidazole group is reacted with the iodine-terminated copolymer. The dispersibility and reactivity of AlN in the copolymer are increased through the reaction of the imidazole group with iodine, thereby improving the interfacial bonding force between AlN and PVDF matrix, thereby maintaining its mechanical strength and anti-aging ability at a high level.
[0078] Experimental Example 2
[0079] In this experimental example, the heat dissipation performance of the backplane materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested. After the backplane materials prepared in Examples 1-3 and Comparative Examples 1-3 were made into finished film samples, a heating plate was attached to the center of the lower surface of the finished film sample, and the temperature of the sampling points was measured with a temperature measuring probe according to the five-point sampling method. After the temperature distribution of each point was uniform, the equilibrium time and equilibrium temperature were recorded; the thermal diffusion coefficient was calculated according to the following formula:
[0080] ;
[0081] Where α is the thermal diffusion coefficient of the coating (μm 2 / s); d is the thickness of the coating at the test point (μm); t 50 Indicates the time required for the temperature to reach half of the maximum value (s);
[0082] Figure 4 The heat dissipation performance results of the backplane materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the thermal diffusion coefficient of the backplane materials prepared in Examples 1-3 is 3.0-3.5 μm. 2 ·s -1The thermal diffusion coefficient of the comparative examples 1-3 is 2.63 μm, which has good heat dissipation performance. 2 ·s -1 , 2.18μm 2 ·s -1 , 2.81μm 2 ·s -1 Due to the uneven dispersion of AlN and the poor interface bonding performance with the PVDF matrix, the diffusion of phonons is blocked, which in turn reduces the diffusion of heat, resulting in high local temperatures and a decrease in the performance of the photovoltaic backplane.
[0083] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0084] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A solar light conversion silicon-containing backplane material, characterized in that: The raw materials for preparing the silicon-containing backplane material include the following components in parts by weight: 50-70 parts of VDF, 4-6 parts of perfluorooctyltrimethoxysilane, 2-8 parts of tetraethyl orthosilicate, 4-6 parts of KH570, 1-2 parts of modified AlN, 3-5 parts of emulsifier, 5-10 parts of perfluorohexyl iodide, 1-2 parts of buffer, 1-3 parts of initiator, and 0.5-1.5 parts of auxiliary agent.
2. The solar light conversion silicon-containing backplane material according to claim 1, characterized in that: The preparation method of the modified AlN specifically comprises the following steps: A1. Dissolve 3-glycidyloxypropyltriethoxysilane in DMSO, stir the mixture at 200-300 rpm under nitrogen atmosphere, slowly drop 4-aminoimidazole, mix well, add TEA to adjust the pH to 8-9, raise the reaction temperature to 40-50°C, stir the mixture for 4-8h, remove the reaction solvent by distillation under reduced pressure, add ethyl acetate for washing, and purify to obtain grafted triethoxysilane; A2. Add AlN to a planetary ball mill, add ethanol solution, and perform ball milling at a speed of 600-800 rpm. After 1-2 hours, add the grafted triethoxysilane prepared in step S1, and continue ball milling. After 3-5 hours, after the ball milling is cooled, place it at 120-150° C. for vacuum drying. After drying for 10-12 hours, modified AlN is obtained.
3. The solar light conversion silicon-containing backplane material according to claim 2, characterized in that: In step A1, the mass concentration of 3-glycidyloxypropyltriethoxysilane in DMSO is 20-28 mg / mL.
4. The solar light conversion silicon-containing backplane material according to claim 3, characterized in that: In step A1, the added mass of the 4-aminoimidazole is 28%-43% of the mass of 3-glycidyloxypropyltriethoxysilane; the mass concentration of the 4-aminoimidazole in DMSO is 40-60 mg / mL.
5. The solar light conversion silicon-containing backplane material according to claim 4, characterized in that: In step A2, the ethanol solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 10-20:
1.
6. The solar energy conversion silicon-containing backplane material according to claim 5, characterized in that: In step A2, the mass volume ratio between the AlN and the ethanol solution is 1.1-1.8 g / mL; the mass volume ratio between the AlN and the grafted triethoxysilane is 6-10 g / mL.
7. The solar energy conversion silicon-containing backplane material according to claim 6, characterized in that: The emulsifier includes at least one of sodium lauryl sulfate, sodium laureth sulfate, Tego Wet 265, and BYK-348; The buffer comprises at least one of NaHCO3 and NH4HCO3; The initiator includes at least one of ammonium persulfate, sodium persulfate, and potassium persulfate; The auxiliary agent includes at least one of sodium bisulfite and ferrous sulfate.
8. A method for preparing a solar energy conversion silicon-containing backplane material according to any one of claims 1 to 7, characterized in that: The specific steps include: S1. Dissolve perfluorooctyltrimethoxysilane, ethyl orthosilicate and KH570 in anhydrous ethanol, mix well, raise the reaction temperature to 70-80°C, adjust the pH of the reaction system to 4-5 with HCl, stir the reaction at 150-180 rpm, add 50-70 mL of deionized water dropwise, continue the reaction for 5-7 hours, and remove the reaction solvent by rotary evaporation to obtain a siloxane reaction solution; S2, add deionized water, emulsifier and buffer to the reactor, introduce nitrogen, add the siloxane reaction solution prepared in step S1, stir the siloxane reaction solution at 400-500 rpm to disperse it evenly, add perfluorohexyl iodide at room temperature, increase the temperature to 70-90°C, add VDF, maintain the reaction temperature, add initiator and auxiliary agent, react for 6-8h, cool to room temperature, remove unreacted substances, add ethanol / NaCl aqueous solution for washing, adjust the pH to 3-4, place at room temperature for static sedimentation treatment, vacuum filter, wash with anhydrous ethanol and deionized water in turn, and vacuum dry to obtain PVDF / siloxane copolymer; S3, adding the modified AlN into DMF, adding K2CO3, and fully dispersing the modified AlN at a speed of 300-400 rpm to obtain an activated modified AlN solution; S4, dissolving the PVDF / siloxane copolymer prepared in step S2 in DMF, raising the temperature to 80-100°C, fully dissolving the PVDF / siloxane copolymer at a speed of 200-300rpm, adding dropwise the activated modified AlN solution prepared in step S3, raising the reaction temperature to 100-120°C, stirring the reaction at a speed of 400-600rpm for 12-24h, cooling to room temperature, adding deionized water for washing, filtering, washing with anhydrous ethanol and ethyl acetate in sequence, and vacuum drying to obtain a photovoltaic backplane material.
9. The method for preparing a solar light conversion silicon-containing backplane material according to claim 8, characterized in that: In step S3, the mass concentration of AlN in DMF is 10-20 mg / mL.
10. The method for preparing a solar light conversion silicon-containing backplane material according to claim 9, characterized in that: In step S3, the mass ratio of K2CO3 to modified AlN is 0.3-0.5:1.
Citation Information
Patent Citations
Infrared radiating coating for photovoltaic module backing plate and preparation method of radiating photovoltaic module backing plate
CN104231701A
Blend film containing graphene and preparation method thereof
CN105218987A
Radiation self-cooling solar battery back sheet film and preparation method thereof
CN110391310A